2000
DOI: 10.1046/j.1365-2222.2000.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of once daily dosing with inhaled budesonide on airway hyperresponsiveness and airway inflammation following repeated low‐dose allergen challenge in atopic asthmatics

Abstract: Both budesonide 100 microg and 400 microg inhaled once daily significantly reduces allergen-induced sputum eosinophilia after repeated low dose challenge; however, only the higher dose also attenuates the allergen-induced airway hyperresponsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
7
20
0
Order By: Relevance
“…Accordingly, the baselines were very similar for all outcome variables and statistical calculations yielded the same final results irrespective of adjustments for baseline differences. With a three-period design and 4 days of allergen-PD5 exposure, GAUVREAU et al [18] demonstrated sufficient washout with 1 week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the baselines were very similar for all outcome variables and statistical calculations yielded the same final results irrespective of adjustments for baseline differences. With a three-period design and 4 days of allergen-PD5 exposure, GAUVREAU et al [18] demonstrated sufficient washout with 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…In this challenge setting, patients with allergic asthma inhale fixed doses of allergen that are titrated to cause minimal bronchoconstriction and administered once daily on between four and 10 consecutive weekdays [17,18]. The procedure generates increased airway hyperresponsiveness to direct bronchoconstrictors and elevations in exhaled nitric oxide fraction (FeNO) and in inflammatory markers in sputum [17,18].…”
mentioning
confidence: 99%
“…However, investigations of mechanisms of airway inflammation in this particular model have been rather limited so far, and findings in peripheral blood are largely negative [5,7,9]. In a diluent controlled evaluation of the challenge, the percentage of eosinophils, interleukin-5 and eosinophil cationic protein in induced sputum were shown to increase [2], and early effects on eosinophils and macrophages in bronchoalveolar lavage fluid have also been reported [9,10].…”
mentioning
confidence: 90%
“…The challenge model is, therefore, particularly suitable to investigate early events in the development of AHR, a central feature of the asthmatic phenotype. The relevance of the model is supported by the established effects of inhaled corticosteroids on AHR and sputum eosinophilia induced by the low-dose challenge procedure [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation